Blue crimes and ocean harmscapes: strategies for tackling Transnational Maritime Environmental Crimes in the Global South - Hübschle, Annette; Lindley, Jade (Frontiers in Conservation Science, 2024)
Transnational Maritime Environmental Crimes (TMEC) pose a significant threat to marine ecosystems, biodiversity, and the socio-economic sustainability of coastal communities, particularly in the Global South. These crimes, including illegal, unreported, and unregulated (IUU) fishing and the trafficking of marine species, demand innovative and inclusive governance strategies. This paper employs a multi-method approach, incorporating a comprehensive literature review and two case studies: IUU fishing in the Philippines and sea cucumber trafficking in the Seychelles. The carrot-and-stick approach, alongside whole-of-society perspectives and principles of southern blue criminology, is used to analyze the effectiveness of regulatory frameworks and incentives aimed at reducing TMEC. Findings from the case studies indicate that regulatory frameworks alone are insufficient to combat TMEC. The integration of community-based strategies, incentives for compliance, and penalties for violations fosters behavioral change among states and individuals. The whole-of-society approach, involving governments, corporations, civil society, and local communities, proves critical in designing effective regulatory measures. By leveraging the carrot-and-stick methodology and emphasizing the inclusion of all stakeholders, this paper highlights the potential for gender-sensitive, socio-ecologically informed solutions that align with Sustainable Development Goal 14. The integration of southern blue criminology principles ensures that governance frameworks are tailored to the unique socio-economic contexts of the Global South, promoting global cooperation to combat TMEC and protect marine environments.